Persepsi Orang Rimba Terhadap Hutan dan Pengaruhnya Terhadap Sistem Sosial - Takiddin Takiddin (Buletin Al-Turas, 2012)
Forest people perceive forests asliving quarter stomaintaint their existence is the face of the earth. They saw the forest as their homes. They do not have a permanent home, as usual modern humanism general. They made the house just enough to protect them from rain and heat. Their house isshapedlike a very simple ordinary tents they calls udung. Their perception of space also affect show these tribes make ends meet. Traditionally basically staple food needs and another needs can be metby the forest. Their traditional way of life consists of hunting and gathering.